Photo-fabricated structure, material for photo-fabrication, and method of manufacturing photo-fabricated structure
Patent Information
- Application Number
- JP2023129270
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2025-02-21
AI Technical Summary
【0009】 本発明の一実施形態によれば、より機械的強度に優れた光造形構造体が提供される。また、本発明の一実施形態に係る光造形用材料および光造形構造体の製造方法によれば、より機械的強度に優れた光造形構造体を製造可能である。
Smart Images

Figure 2025024899000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a photo-fabricated structure, a material for photo-fabricated structure, and a method for manufacturing a photo-fabricated structure. [Background technology]
[0002] 2. Description of the Related Art A method for forming a nano-level photo-fabricated structure by generating a two-photon excitation phenomenon using a femtosecond laser, and a photo-fabricated structure produced by this method have been known (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2002-69665 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, miniaturization of devices has been promoted in many technical fields, and accordingly, the manufacture of parts having microstructures has become important. The present inventors have found that stereolithography using two-photon excitation phenomenon is useful in the manufacture of such microstructures. On the other hand, the strength of the microstructure may be required in order for the microstructure to function as a part.
[0005] The present invention has been made in view of the above problems. That is, a main object of the present invention is to provide a photo-fabricated structure having superior mechanical strength, a photo-fabricated material capable of producing the photo-fabricated structure, and a method for producing the photo-fabricated structure. [Means for solving the problem]
[0006] In order to achieve the above object, in one embodiment of the present invention, A photo-fabricated structure containing one or more metal elements as a main component, The photo-molded structure has a pore area ratio in the range of 20% or less.
[0007] In addition, in one embodiment of the present invention, A metal material containing metal ions of one or more metal elements, nanoparticles, and a medium containing the metal material and the nanoparticles, A material for stereolithography is provided in which the thermal conductivity of the nanoparticles is greater than the thermal conductivity of the main component of the medium.
[0008] In addition, in one embodiment of the present invention, The method includes a step of irradiating a laser beam onto a material for optical shaping, the optical shaping material comprises a metal material containing metal ions of one or more metal elements, nanoparticles, and a medium containing the metal material and the nanoparticles; The thermal conductivity of the nanoparticles is greater than the thermal conductivity of the main component of the medium. Effect of the Invention
[0009] According to one embodiment of the present invention, a photo-molded structure having superior mechanical strength is provided. Also, according to the photo-molded material and the method for manufacturing a photo-molded structure according to one embodiment of the present invention, a photo-molded structure having superior mechanical strength can be manufactured. [Brief description of the drawings]
[0010] [Figure 1A] FIG. 1A is a schematic diagram showing a method for producing a photo-molded structure according to one embodiment of the present invention. [Figure 1B] FIG. 1B is a schematic diagram showing a method for producing a photo-molded structure according to one embodiment of the present invention. [Figure 1C] FIG. 1C is a schematic diagram showing a method for producing a photo-molded structure according to one embodiment of the present invention. [Diagram 2] FIG. 2 is an absorption spectrum of a nanoparticle-free stereolithography material according to one embodiment of the present invention. [Diagram 3]FIG. 3 is an absorption spectrum of a stereolithography material including nanoparticles according to one embodiment of the present invention. [Figure 4] FIG. 4 is a SEM photograph of a photo-fabricated structure according to one embodiment of the present invention. [Diagram 5] FIG. 5 is a SEM photograph of a photo-fabricated structure according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The optically shaped structure, the optically shaped material, and the method for manufacturing the optically shaped structure of the present invention will be described in detail below. Although the description will be made with reference to the drawings as necessary, the contents shown in the drawings are merely schematic and illustrative for understanding the present invention, and the appearance and dimensional ratios may differ from the actual products.
[0012] As used in this specification, "plan view" or "plan view shape" is based on a sketch of an object viewed from above or below along the laser irradiation direction (i.e., the up-down direction in Figures 1A to 1C).
[0013] The present invention relates to a technology called "stereolithography" for producing a three-dimensional structure using a laser beam. In other words, "stereolithography" is a modeling technique for forming a structure by irradiating a laser beam. By irradiating a laser beam of a specific wavelength onto a material for stereolithography, it is possible to easily integrally form, for example, a two-dimensional structure such as a thin film of any shape, or a three-dimensional structure formed by stacking two-dimensional structures. In the present invention, the "stereolithography structure" refers to a structure formed by such stereolithography.
[0014] More specifically, the present invention relates to photo-fabrication using the two-photon absorption phenomenon. The two-photon absorption phenomenon is a phenomenon in which a molecule absorbs two photons simultaneously and is excited. The efficiency of such two-photon absorption is proportional to the square of the applied optical electric field. Therefore, when a laser is irradiated onto a two-dimensional plane, two-photon absorption occurs only in the region where the electric field intensity at the center of the laser spot exceeds a predetermined intensity, and two-photon absorption does not occur in the surrounding region where the electric field intensity is relatively weak. In a three-dimensional space, when a laser beam is focused by a lens, two-photon absorption occurs only in the region where the electric field intensity at the center of the laser spot of the focused laser beam exceeds a predetermined intensity. On the other hand, two-photon absorption does not occur in the surrounding region where the electric field intensity is low except for the center of the laser spot. That is, in photo-fabrication using the two-photon absorption phenomenon, a metal material can be excited only in an extremely narrow region of the focus of the laser beam, making it possible to achieve modeling with high spatial resolution. This makes it possible to form a fine three-dimensional structure on the order of nanometers or microns.
[0015] In the following, we will first explain the basic method for producing a photo-fabricated structure by two-photon absorption (hereinafter, simply referred to as "photo-fabricating method") and the photo-fabricating material used in the production of the photo-fabricated structure. However, the method for producing a photo-fabricated structure described here is merely an example for understanding the invention and does not limit the invention.
[0016] [Basic manufacturing method for photolithography structures] The method for manufacturing a photo-molded structure includes a step of irradiating a laser beam through a lens to a photo-molding material including a metal material and a medium containing the metal material. This step causes a two-photon absorption phenomenon at the focal position of the laser beam, and a photo-molded structure containing one or more metal elements contained in the metal material is formed. The "photo-molding material" is a material for manufacturing a photo-molded structure by laser irradiation, and can also be called a "photosensitive material" or a "material for manufacturing a photo-molded structure". In this step, the photo-molded structure can be formed at any desired location by moving the focal position of the laser beam within the photo-molding material. In other words, a photo-molded structure of a desired shape can be formed by irradiating the laser beam while moving the focal position at a predetermined scanning speed so that the photo-molded structure is formed only at any desired location in the photo-molding material.
[0017] The light source of the laser light is preferably a laser with an ultrashort pulse light of femtoseconds or less, and specific examples of the light source include a femtosecond titanium sapphire laser, a UV femtosecond laser, and a green femtosecond laser.
[0018] In the process of manufacturing a photo-fabricated structure, the wavelength of the laser light is determined according to the excitation wavelength of the metal material used. For example, the wavelength of the laser light may be twice the absorption wavelength of the metal material so that the metal material undergoes two-photon absorption.
[0019] In this method, after the metal material is excited by two-photon absorption occurring at the focal position, the metal material contained in the photo-fabrication material reacts with the heat released in the deactivation process, and fine particles of a metal compound can be generated. After that, the fine particles are heated in association with the two-photon absorption phenomenon caused by laser irradiation, and an integrated model can be formed. That is, in this method, the generation and firing of the metal compound fine particles can be performed in one step by laser irradiation. Therefore, in this method, a firing step of the photo-fabrication structure is not necessarily required. On the other hand, this method may include a step of separately firing the photo-fabrication structure obtained by laser irradiation.
[0020] The method may further include a step of preparing a photo-molding material by mixing a metal material with a medium before the step of irradiating the laser light. If necessary, the method may further include a step of preparing a coated product containing at least a metal element contained in the metal material by coating the photo-molding material. In this case, the photo-molding material further includes a substrate to be coated, and a medium containing a metal material is disposed on the substrate. Thereafter, a photo-molding structure can be prepared on the substrate by irradiating the photo-molding material with a laser light from the medium side.
[0021] In the step of producing the coated product, the medium on the substrate may or may not be evaporated.
[0022] When a laser beam is irradiated onto a photo-lithography material in a state where the medium has not evaporated and remains on the substrate, the energy provided by the laser beam is also used to increase the temperature of the medium. Therefore, when a laser beam is irradiated onto a photo-lithography material in a state where the medium has evaporated (i.e., the substrate and the metal material), a photo-lithography structure can be formed using a laser beam with a lower output than when a laser beam is irradiated onto a photo-lithography material in a state where the medium remains.
[0023] On the other hand, when a laser beam is irradiated onto a photo-molding material in a state where the medium has been evaporated, the medium containing the metal material is no longer present around the photo-molding structure after the laser beam is irradiated, so that a structure having two or more layers cannot be continuously produced as it is. In contrast, by leaving the medium without evaporating it, the photo-molding material can be present around the photo-molding structure even after the laser beam is irradiated. Therefore, for example, when a liquid or gel medium is used, the medium remaining around the structure can flow onto the photo-molding structure once formed, so that a photo-molding structure having two or more layers can be produced as it is. In other words, the process of newly disposing a photo-molding material on the structure in order to form a structure having two or more layers can be omitted. As a result, a three-dimensional photo-molding structure having a height of, for example, several tens of μm or more can be produced.
[0024] [Basic materials for stereolithography] The optical shaping material includes a metal material containing metal ions of one or more metal elements and a medium, and the metal material may be dispersed in the medium. For example, the metal element contained in the metal material preferably has a melting point of 400°C or higher. By having a melting point of 400°C or higher, it is possible to prevent the metal material from volatilizing due to heat generated by irradiation with a laser beam. The metal element may be at least one selected from the group consisting of iron (Fe), cobalt (Co), copper (Cu), manganese (Mn), nickel (Ni), zinc (Zn), titanium (Ti), and barium (Ba). For example, hydroxides, acetates, chlorides, nitrates, sulfates, chelates, and / or complex salts of such metal elements may be used as the metal material.
[0025] The metal material may be a material that is excited at a specific wavelength. More preferably, the metal material may be a two-photon absorbing material. The two-photon absorbing material refers to a material that can excite molecules at a specific wavelength, and in which the actual excited state exists at an energy level twice that of the photon used for the excitation. By using a two-photon absorbing metal material, a photo-molded structure can be formed only in a very narrow region at the focus of the irradiated laser light, and a finer photo-molded structure can be obtained.
[0026] The medium of the photo-molding material can be a liquid, gel or solid. Preferably, the metal material is dispersed in the medium. In other words, the medium may be a liquid, gel or solid containing the metal material dispersed in the medium. By containing the metal material in a liquid, gel or solid, it becomes possible to suitably arrange the metal material in the medium, and therefore, by irradiating the medium with a laser beam, a three-dimensional photo-molded structure can be easily formed.
[0027] When the medium is liquid, it may be an inorganic medium such as water, or an organic medium such as alcohol, and the medium may consist of only one material, or may be a mixed medium containing two or more compounds.
[0028] For example, when the medium containing the metallic material is a gel, the medium can be in a state in which the metallic materials in the medium are cross-linked to each other and retain moisture, or when the medium containing the metallic material is a solid, the medium containing the metallic material can be a dry gel in which moisture and solvent have been evaporated and concentrated from the gel.
[0029] The medium may further contain a dispersant. Examples of dispersants include polyvinylpyrrolidone, polyvinyl alcohol, and polyacrylic acid. The dispersant may be one type, or two or more types may be used. In one embodiment, the dispersant preferably contains polyvinylpyrrolidone. By mixing the dispersant into the medium, metal ions are suitably dispersed in the medium, making it easier to fabricate a stereolithography structure with a more uniform structure. Furthermore, the viscosity of the material solution may be increased by mixing a dispersant such as polyvinylpyrrolidone (PVP) into the medium. By increasing the viscosity of the medium, the medium can be easily applied to a substrate to be described later, making it easier to handle the stereolithography material.
[0030] The medium may also contain further additives other than the dispersant, for example, a gelling agent, a thickening agent, or the like.
[0031] The optical shaping material may further include a substrate, and a medium may be disposed on the substrate. For example, a medium containing a metal material may be applied onto the substrate. In other words, the optical shaping material may further include a substrate located below the medium as viewed from the laser incidence side. The substrate material is not particularly limited, and may be, for example, a resin material, a ceramic material, or a metal. The resin material may be, for example, at least one material selected from the group consisting of epoxy resin, phenolic resin, polyimide resin, bismaleimide resin, fluororesin, and polyphenylene oxide resin. The ceramic material may be, for example, at least one material selected from the group consisting of alumina, titania, zirconia, aluminum nitride, silicon nitride, and barium titanate. The metal may be, for example, at least one material selected from the group consisting of iron (Fe), copper (Cu), and aluminum (Al).
[0032] The photo-fabricated structure produced by the above method contains metal elements derived from metal ions.
[0033] For example, when the metal material contains Fe ions, a photo-fabricated structure containing Fe can be manufactured. When the metal material further contains Co ions, Cu ions, Mn ions, Ni ions, or Zn ions, a photo-fabricated structure containing Co, Cu, Mn, Ni, or Zn and Fe can be manufactured. In this manner, a photo-fabricated structure containing any metal element can be manufactured, and a photo-fabricated structure having desired properties (e.g., magnetic properties, etc.) can be manufactured.
[0034] In addition, when the metal material contains Ti ions and Ba ions, a photo-fabricated structure containing Ti and Ba can be fabricated. For example, barium titanate (BaTiO 3 It is possible to fabricate a stereolithographic structure having dielectric properties such as:
[0035] The present inventors have found that a large number of pores are formed on the surface and inside of the photo-printed structure produced as described above, and that if the photo-printed structure contains a large number of such pores, the density of the photo-printed structure decreases, and there is a risk that a photo-printed structure having the desired mechanical strength cannot be obtained (see FIG. 4). In this specification, the term "pore" refers to a pore having an area of 0.05 μm2 or less in a plan view. 2 These are minute cavities (holes). In other words, the photo-molded structure manufactured using the above-mentioned method and material may include a plurality of minute holes. The present inventors have intensively studied a solution for reducing the formation of pores during the manufacturing process of a photo-molded structure and providing a photo-molded structure with superior mechanical strength. As a result, it has been newly discovered that the formation of pores in a photo-molded structure is suppressed by including nanoparticles in the photo-molded material. By suppressing the formation of pores in this way, the present inventors have achieved the achievement of obtaining a photo-molded structure with superior mechanical strength. The photo-molded material of the present invention, the method for manufacturing a photo-molded structure using the photo-molded material, and the photo-molded structure obtained thereby will be described in detail below.
[0036] [The material for photolithography of the present invention] The optical shaping material of the present invention further comprises nanoparticles contained in the medium. That is, the optical shaping material comprises a metal material, nanoparticles, and a medium containing the metal material and the nanoparticles. Here, the "nanoparticles" in the present invention refer to particles having an average particle size of 1 nm or more and 100 nm or less. The nanoparticles may be dispersed in the medium. The thermal conductivity of the nanoparticles contained in the medium is greater than the thermal conductivity of the material that is the main component of the material constituting the medium. That is, the nanoparticles have a thermal conductivity greater than that of the main component of the medium. In other words, the thermal conductivity of the material contained as the main component in the medium is smaller than that of the nanoparticles. The "main component of the medium" refers to the material that has the largest volume ratio among the materials constituting the medium. For example, when the medium is composed of a single material, the thermal conductivity of the nanoparticles is greater than that of the single material. Alternatively, when the medium is a mixed medium containing multiple materials, the thermal conductivity of the nanoparticles is greater than that of the material that has the largest volume ratio in the medium.
[0037] By using a photo-lithography material containing nanoparticles having such a high thermal conductivity, the formation of pores in the photo-lithography structure is suppressed. This makes it possible to provide a photo-lithography structure with superior mechanical strength. Without wishing to be bound by theory, one of the reasons why the number of pores in the photo-lithography structure can be reduced in this way is as follows.
[0038] The present inventors considered that the formation of pores in the stereolithography structure is due to the heating of the material by laser irradiation. As described above, when the stereolithography material is irradiated with a laser, a metal compound is generated by a chemical reaction of the metal material accompanied by heat released by the two-photon absorption phenomenon. At that time, in the area heated by the laser irradiation, the metal compound is generated and at the same time a by-product gas may be generated. In other words, gas may be generated in the area where the heat generated by the laser irradiation is diffused. The wider the area where the heat is diffused, the easier it is to form a stereolithography structure in a state where the generated by-product gas is contained. As a result, pores may be formed in the area where the gas was contained.
[0039] The present inventors conducted intensive studies based on the consideration of the pore formation process, and as a result, they realized the narrowing of the thermal diffusion region A by making nanoparticles with high thermal conductivity exist in the stereolithography material (see Figs. 1A to 1C). By making nanoparticles 12 with higher thermal conductivity contained in the stereolithography material 10, the heat generated by the laser irradiation L can be preferentially accumulated in the nanoparticles 12 (see Figs. 1A and 1B). Therefore, compared to the case where the nanoparticles 12 are not contained, the diffusion of heat generated by the laser irradiation in the stereolithography material 10 can be suitably suppressed. This makes it possible to apply heat more locally in the stereolithography material, and therefore it is possible to suitably suppress the inclusion of gas in the stereolithography structure. As a result, the formation of pores in the stereolithography structure can be suppressed. Therefore, a stereolithography structure with higher density and excellent mechanical strength can be provided.
[0040] Furthermore, by narrowing the thermal diffusion area by adding nanoparticles, the thermal energy generated by laser irradiation is more easily concentrated in a narrower area. This makes it possible to cause the reaction that forms the photo-fabricated structure by laser irradiation in a narrower area. This makes it possible to fabricate a photo-fabricated structure with higher resolution.
[0041] In a preferred embodiment, the thermal conductivity of the nanoparticles may be greater than that of the medium and the metal material. In other words, in the photo-molding material, the thermal conductivity of the medium and the metal material may be less than that of the nanoparticles. For example, the nanoparticles may have the greatest thermal conductivity among the medium and the materials contained in the medium. Alternatively, among the components contained in the photo-molding material, the nanoparticles contained in the medium may have the greatest thermal conductivity. According to this configuration, the heat generated by the laser irradiation can be efficiently accumulated by the nanoparticles, so that the effect of narrowing the thermal diffusion region in the photo-molding material can be more significantly obtained. This further suppresses the formation of pores caused by thermal diffusion, making it possible to obtain a photo-molded structure with higher density and excellent mechanical strength.
[0042] The thermal conductivity of the nanoparticles can be 5 times or more, 50 times or more, or 500 times or more, preferably 10 times or more, more preferably 100 times or more, of the thermal conductivity of the main component of the medium. When the thermal conductivity of the nanoparticles is within the above-mentioned range, a photo-molded structure with fewer pores can be suitably obtained. On the other hand, when the efficiency of laser irradiation during the production of a photo-molded structure is emphasized, the thermal conductivity of the nanoparticles may be 5000 times or less than the thermal conductivity of the medium. When the thermal conductivity of the nanoparticles is within the above-mentioned range, heat is suitably applied to the metal material in the medium, and the generation of fine particles of the metal compound and the subsequent firing can be more efficiently performed, while a photo-molded structure with better mechanical strength can be obtained.
[0043] The thermal conductivity of the nanoparticles may be greater than that of the mixture of the metal material and the medium. That is, the thermal conductivity of the nanoparticles may be greater than that of the medium containing the metal material. This means that the thermal conductivity of the medium containing components other than the nanoparticles in the photo-molding material is smaller than that of the nanoparticles to be added. The thermal conductivity of the nanoparticles can be 5 times or more, 50 times or more, or 500 times or more, preferably 10 times or more, more preferably 100 times or more, of the thermal conductivity of the medium containing the metal material. When the thermal conductivity of the nanoparticles is within the above range, a photo-molded structure with fewer pores can be suitably obtained. On the other hand, when the efficiency of laser irradiation during the manufacture of the photo-molded structure is emphasized, the thermal conductivity of the nanoparticles may be 5000 times or less than that of the metal material. When the thermal conductivity of the nanoparticles is within the above range, heat is suitably applied to the metal material, and a photo-molded structure with better mechanical strength can be obtained while more efficiently generating the metal compound.
[0044] The thermal conductivity of the nanoparticles may be greater than that of the substrate located under the medium as viewed from the laser incidence side. In other words, the thermal conductivity of the substrate may be smaller than that of the nanoparticles. When the thermal conductivity of the nanoparticles is greater than that of the substrate, the heat generated by the laser irradiation is absorbed by the substrate, and the thermal energy given to the metal material may be relatively small. If the thermal energy given to the metal material is insufficient, it becomes difficult to form a photo-molded structure, so the laser output is inevitably increased. When a high-power laser is applied to the photo-molding material, the formation of the photo-molded structure tends to proceed more rapidly, and as a result, pores may be easily formed in the photo-molded structure. By making the thermal conductivity of the nanoparticles greater than that of the substrate, it is possible to more suitably prevent the absorption of heat into the substrate and to suitably suppress the thermal diffusion in the photo-molding material. Therefore, a photo-molded structure with fewer pores and excellent mechanical strength can be obtained while suppressing the laser output.
[0045] The thermal conductivity of the nanoparticles can be 2 times or more, 5 times or more, or 10 times or more than the thermal conductivity of the substrate. When the thermal conductivity of the nanoparticles is within the above range, a photo-molded structure with fewer pores can be suitably obtained. On the other hand, when the efficiency of laser irradiation during the production of a photo-molded structure is emphasized, the thermal conductivity of the nanoparticles may be 50 times or less, 45 times or less, or 40 times or less than the thermal conductivity of the substrate. When the thermal conductivity of the nanoparticles is within the above range, heat is suitably applied to the metal material, and the production of the metal compound can be more efficiently carried out, while a photo-molded structure with fewer pores and excellent mechanical strength can be obtained.
[0046] Specifically, the thermal conductivity of the nanoparticles can be, for example, 10 W / m·K or more, 20 W / m·K or more, or 50 W / m·K or more. When the thermal conductivity of the nanoparticles is within the above-mentioned range, the thermal diffusion in the stereolithography material can be suitably suppressed. In addition, the upper limit of the thermal conductivity is not particularly limited, but can be, for example, 500 W / m·K or less, 450 W / m·K or less, or 400 W / m·K or less.
[0047] The substrate may have a thermal conductivity smaller than that of the medium applied on the substrate, or the thermal conductivity of the substrate may be larger than that of the medium. In a preferred embodiment, the thermal conductivity of the substrate is smaller than that of the medium. This allows the heat energy to be applied to the medium more efficiently without the heat generated by the laser irradiation being diffused to the substrate.
[0048] The thermal conductivity can be a known value or a value measured by a known method. For example, the thermal conductivity can be measured by a known method such as a steady-state method or a non-steady-state method, and an appropriate method may be selected depending on the properties of the material to be measured. For example, the thermal conductivity can be measured by a steady-state method such as a heat flow meter method, or a non-steady-state method such as a laser flash method, a periodic heating method, or a hot wire method.
[0049] The nanoparticles may be crystalline or amorphous. The material of the nanoparticles is not particularly limited, and an optimal material can be selected depending on the photo-fabricated structure to be manufactured. For example, the nanoparticles may be a metal material such as gold nanoparticles, or may be a resin material, a glass material, a ceramic material, or the like.
[0050] In a preferred embodiment, the nanoparticles contain a metal element contained in the metal material. That is, the nanoparticles may contain at least one of the metal elements contained in the metal material. In other words, the same metal element may be contained in the metal material and the nanoparticles. More preferably, the nanoparticles may be composed of elements contained in the composition of the metal material. When nanoparticles are contained in the photo-molding material, the photo-molded structure manufactured using the material may contain the nanoparticles. By the nanoparticles having a metal element common to the metal material, it is possible to suppress the incorporation of metal elements other than the elements contained in the metal material into the photo-molded structure. This makes it possible to obtain a photo-molded structure having excellent mechanical strength while more suitably suppressing the incorporation of impurities into the photo-molded structure.
[0051] For example, the nanoparticles preferably have a melting point of 400° C. or higher. By having a melting point of 400° C. or higher, volatilization due to heat caused by irradiation with laser light can be suppressed.
[0052] The content of nanoparticles in the medium is 5.0 × 10 relative to the total volume of the medium including the metal material and nanoparticles. -6 Volume percent or more: 7.0×10 -6 % by volume or more, or 1.0×10 -5 % or more by volume. When the content of the nanoparticles is within the above range, the thermal diffusion region can be suitably narrowed, and a photo-fabricated structure having excellent mechanical strength can be obtained. In addition, the content of the nanoparticles contained in the medium can be 1.0×10 to 1.0×10 based on the total volume of the medium containing the metal material and the nanoparticles. -3 Volume percent or less, 7.0 x 10 -4 Mass% or less, or 5.0 x 10 -4When the content of the nanoparticles is within the above range, a photo-molded structure having a more uniform composition and excellent mechanical strength can be obtained.
[0053] It is preferable that the nanoparticles are used in a range where the addition of the nanoparticles does not affect the light absorption spectrum of the stereolithography material. In other words, in a stereolithography material containing a metal material capable of exciting molecules at a specific wavelength, it is preferable that the addition of the nanoparticles does not change the light absorption characteristics of the metal material.
[0054] FIG. 2 shows the absorption spectrum of a solution using barium acetate and tetraisopropyl orthotitanate (TTIP) as metal materials. FIG. 3 shows the absorption spectrum obtained for a stereolithography material in which 15 ppm of gold nanoparticles were further added to the medium used in the measurement of FIG. 2. As shown in FIG. 2, the stereolithography material containing the above metal material has a peak near 265 nm, but does not have a peak near 520 nm, which is twice the peak wavelength. Therefore, it can be seen that by irradiating the solution with a laser having a wavelength of about 520 nm, a two-photon absorption phenomenon occurs, making it possible to obtain a stereolithography structure.
[0055] On the other hand, the absorption spectrum of FIG. 3 after the addition of nanoparticles shows almost no peaks derived from nanoparticles compared to the absorption spectrum of FIG. 2. The absorption spectrum of FIG. 3 also shows a peak near 265 nm, as in the absorption spectrum of FIG. 2, and no peak is observed near 520 nm, which is twice the peak wavelength. That is, the light absorption characteristics of the stereolithography material are almost unchanged before and after the addition of nanoparticles. This is because the content of gold nanoparticles is sufficiently low compared to the content of the metal material contained in the medium, and the absorbance of gold nanoparticles is almost negligible compared to the absorbance of the metal material. By using a stereolithography material having such an absorption spectrum, the laser light irradiated to the stereolithography material can excite the metal material suitably without being substantially affected by the addition of nanoparticles.
[0056] In addition, by using nanoparticles that do not absorb the wavelength of the irradiated laser, it is possible to suppress the decrease in the laser light intensity at the focal position. In other words, it is possible to suppress the absorption of the laser light by nanoparticles that are at the focal position and in front of the focal position. Here, "not absorbing the wavelength of the irradiated laser" also includes the case where the absorption intensity of the nanoparticles is at a negligible level compared to the peak intensity of the medium containing the metal material. For example, the absorption intensity of the nanoparticles can be 3.0% or less, 2.5% or less, or 2% or less of the peak intensity of the medium containing the metal material.
[0057] [Method of manufacturing a photo-molded structure of the present invention] In the method for producing a photo-molded structure of the present invention, a photo-molded structure is produced using the above-mentioned photo-molding material. More specifically, in this method, a photo-molding material containing nanoparticles in a medium having a higher thermal conductivity than the main component of the medium is used. A photo-molded structure is produced by irradiating such a photo-molded material with a laser beam. FIGS. 1A to 1C are schematic diagrams showing a part of a method for producing a photo-molded structure according to one embodiment of the present invention. The presence of nanoparticles 12 having a high thermal conductivity in the photo-molding material 10 can suppress the diffusion of heat caused by the two-photon excitation phenomenon caused by the laser irradiation L. In other words, the diffusion region A of the thermal energy released due to the two-photon excitation phenomenon can be made narrower. This makes it possible to further narrow the range in which the photo-molded structure 20 is formed, thereby suppressing the inclusion of the gas generated as a by-product in the photo-molded structure 20. As a result, the formation of pores in the photo-molded structure 20 is suppressed, and a photo-molded structure having superior mechanical strength can be produced.
[0058] Furthermore, by narrowing the thermal diffusion region by adding nanoparticles, the thermal energy generated by laser irradiation is more easily concentrated in a narrower region. As a result, even when a laser beam with a smaller output is used, the thermal energy is efficiently concentrated in a very small region, making it possible to form a photo-fabricated structure. In other words, by adding nanoparticles with high thermal conductivity to the photo-fabricated material, the output of the laser beam for forming the photo-fabricated structure can be made smaller.
[0059] For example, in the step of forming a photo-molded structure by irradiating a laser beam, the output of the irradiated laser can be 100 mW or less, 80 mW or less, 50 mW or less, or 40 mW or less. Even if the laser output is within the above range, the presence of nanoparticles concentrates thermal energy, so that a photo-molded structure can be suitably formed. That is, a photo-molded structure with higher energy efficiency can be manufactured. In addition, since a laser with a relatively small output can be used, the thermal energy released at the focal position of the laser (i.e., the center of the laser spot) becomes relatively small, and thermal diffusion can be more suitably suppressed. As a result, pore formation in the photo-molded structure is suppressed, so that a photo-molded structure with excellent mechanical strength can be obtained.
[0060] The lower limit of the laser output is not particularly limited as long as the photo-molded structure can be formed. In other words, the lower limit of the laser output is not particularly limited as long as the laser irradiation can provide enough energy to form fine particles of a metal compound. For example, the laser output can be 15 mW or more, 20 mW or more, or 25 mW or more.
[0061] In addition, in the method for producing a photo-molded structure of the present invention, the photo-molding material can be suitably produced while moving the focal position of the laser at a faster speed. The moving speed of the focal position can also be called the scanning speed of the laser, and is related to the length of the laser irradiation time at one location. The faster the scanning speed, the shorter the laser irradiation time at one location. On the other hand, the slower the scanning speed, the longer the laser irradiation time at one location. If the scanning speed of the laser is too slow, the laser light is irradiated at one location for a long time, and excessive energy may be given to the photo-molding material. Therefore, if energy efficiency and processing efficiency are emphasized, it is preferable that the scanning speed of the laser is fast. However, in the conventional production method, if the scanning speed is too fast, the laser irradiation time at one location becomes short, so that sufficient energy is not given to the photo-molding material, and there is a risk that the photo-molding structure will not be formed.
[0062] In the method for producing a photo-molded structure of the present invention, since the presence of nanoparticles concentrates thermal energy, even if the laser irradiation time is relatively short, a sufficient amount of energy for forming a photo-molded structure can be suitably secured. Therefore, even if the laser scanning speed is fast, a photo-molded structure can be suitably formed. This makes it possible to efficiently produce a photo-molded structure at a faster processing speed.
[0063] For example, the scanning speed of the laser can be 0.01 mm / s or more and 5.0 mm / s or less, 0.05 mm / s or more and 3.0 mm / s or less, or 0.1 mm / s or more and 2.0 mm / s or less. This means that the focal position of the laser light moves at a speed of 0.01 mm / s or more and 5.0 mm / s or less, 0.05 mm / s or more and 3.0 mm / s or less, or 0.1 mm / s or more and 2.0 mm / s or less. By setting the scanning speed of the laser in the above range, it is possible to manufacture a photo-fabricated structure with better processing efficiency while suppressing the formation of pores.
[0064] [Photo-fabricated structure of the present invention] 4 and 5 are SEM photographs taken at a magnification of 5000 times of the photo-molded structure according to one embodiment of the present invention. As described above, the photo-molded structure 20 of the present invention has a structure with fewer pores 21 or no pores 21. Specifically, the photo-molded structure obtained by the photo-molded material of the present invention described above and the photo-molded structure obtained by the photo-molded structure manufacturing method of the present invention have a structure with fewer pores or no pores compared to the conventional structure. This increases the density of the photo-molded structure, so that a photo-molded structure with better mechanical strength can be provided. In addition, when the photo-molded structure is made of a material having dielectric properties such as barium titanate, the photo-molded structure can have more suitable dielectric properties by having a structure with fewer pores.
[0065] The photo-molded structure of the present invention has a lower pore area ratio because the number of pores formed in the structure is smaller. The "pore area ratio" is the area ratio of pores per unit area of the photo-molded structure in a predetermined field of view, and can also be simply referred to as the "pore ratio". In other words, the pore area ratio is a percentage of the total area of pores present in a predetermined field of view in the planar area of the photo-molded structure in the field of view. The pore area ratio of the photo-molded structure of the present invention can be 20% or less, 15% or less, 10% or less, or 8% or less. The lower limit of the pore area ratio of the photo-molded structure of the present invention may be, for example, 0% (i.e., substantially no pores), 0.01% or more, or 0.05% or more. By having the pore area ratio in the above-mentioned range, a photo-molded structure that is denser and has excellent mechanical strength can be obtained.
[0066] The pore area ratio can be measured as follows. A scanning electron microscope (SEM) photograph is taken of any surface or cross section of the photo-molded structure. The obtained SEM photograph can be analyzed using image analysis software to determine the pore area ratio. For example, the SEM photograph is binarized and analyzed to calculate the total area of the parts recognized as pores, and the ratio of the total area of the pores to the planar area of the photo-molded structure in the SEM photograph is calculated, thereby calculating the pore area ratio. As the image analysis software, a known commercially available analysis software may be used. For example, Azo-kun (registered trademark), Winroof, or ImageJ manufactured by Asahi Kasei Engineering Co., Ltd. may be used as the image analysis software.
[0067] When the pore area ratio is obtained from the cross section of the photo-fabricated structure, the cross section may be cut out by subjecting the photo-fabricated structure to focal ion beam processing (FIB processing), and the cross section obtained may be photographed by SEM and the pore area ratio may be calculated by image analysis. For example, a known device such as the FIB processing device SMI3050R by SII NanoTechnology Co., Ltd. may be used for the FIB processing.
[0068] The photo-molded structure of the present invention may contain nanoparticles added to the photo-molded material. In other words, the photo-molded structure of the present invention may contain a trace amount of nanoparticles. The content of the nanoparticles contained in the photo-molded structure is 2.0×10 to the total volume of the photo-molded structure. -5 Volume percent or more, 5.0×10 -5 % by volume or more, or 7.0×10 -5 The content of the nanoparticles in the photo-molded structure can be 2.0×10 or more by volume based on the total volume of the photo-molded structure. -3 Volume percent or less, 1.0 x 10 -3 % by volume or less, or 0.5 x 10 -3 When the content of the nanoparticles is within the above range, a photo-molded structure having a more uniform composition and excellent mechanical strength can be provided.
[0069] In addition, the photo-molded structure of the present invention does not necessarily have to be completely sintered in its entirety. FIG. 5 is an SEM photograph of a photo-molded structure according to one embodiment of the present invention. As shown in the figure, the photo-molded structure 20 may include an unsintered region 25 on at least one of the surface and the interior of the photo-molded structure 20. That is, the photo-molded structure 20 may be partially unsintered and may include fine particles of a metal compound that are not sintered. Such an unsintered region 25 can be formed by applying an amount of energy that can form the photo-molded structure 20 and can leave the unsintered region 25 by laser irradiation. That is, the unsintered region 25 can be formed by applying a laser irradiation that can provide a degree of heat energy that can form the photo-molded structure 20 and does not achieve complete sintering. In the present invention, the photo-molded material contains nanoparticles, which makes it possible to reduce the output of the laser for forming the photo-molded structure, or to increase the scanning speed of the laser, so that the photo-molded structure can be formed with a lower amount of energy, and therefore a photo-molded structure having an unsintered region can be obtained.
[0070] The unsintered regions in the photo-printed structure may have a lower hardness than the sintered regions. Therefore, the unsintered regions in the photo-printed structure may function as stress relief regions that relieve the stress applied to the photo-printed structure. As a result, the mechanical strength of the photo-printed structure as a whole may be improved. EXAMPLES
[0071] A demonstration test was carried out in accordance with the present invention.
[0072] <Example 1> A linear photo-fabricated structure was produced on a base material by the following procedures (1) to (5).
[0073] (1) Barium acetate and TTIP were used as metal materials. A mixed medium containing acetic acid, 2-propanol, and ultrapure water in a volume ratio of approximately 6:1:14 was used as a medium. Gold nanoparticles with an average particle size of 10 nm were used as nanoparticles. (2) Metallic materials and nanoparticles were mixed into the medium. The content of nanoparticles in the medium was 7.0 × 10 relative to the total volume of the medium including the metallic materials and nanoparticles. -5 % by volume. In the mixed solution, the thermal conductivity of the gold nanoparticles (gold) was 295 W / m K, which was significantly higher than that of the mixed medium containing the metal material. Furthermore, the thermal conductivity of ultrapure water, which is the main component of the mixed medium, is 0.602 W / m K. In other words, the thermal conductivity of the nanoparticles contained in the medium was approximately 500 times that of the main component of the medium. (3) A medium containing metal material and nanoparticles was applied to a plate-shaped substrate (SUS) and then dried to produce a dry coating film. (4) The dried coating on the substrate was irradiated with a femtosecond laser using a green femtosecond laser light source. The laser wavelength was 515 nm, and the laser output was 93 mW. The laser irradiation caused a two-photon absorption phenomenon, and the subsequent thermal reaction produced a barium titanate photolithography structure. Furthermore, a line-shaped photolithography structure was obtained by moving the laser focal position in one direction at a scanning speed of 0.5 mm / s. (5) The substrate was washed with pure water to remove any unreacted dried coating.
[0074] <Example 2> A photo-fabricated structure was produced in the same manner as in Example 1, except that the laser output was changed to 75 mW.
[0075] <Example 3> A photo-fabricated structure was produced in the same manner as in Example 1, except that the laser scanning speed was changed to 1.0 mm / s.
[0076] <Example 4> A photo-fabricated structure was produced in the same manner as in Example 1, except that the laser scanning speed was changed to 0.1 mm / s.
[0077] <Example 5> A photo-fabricated structure was produced in the same manner as in Example 1, except that the laser output was changed to 35 mW.
[0078] <Example 6> A photo-fabricated structure was produced in the same manner as in Example 1, except that the laser output was changed to 75 mW and the scanning speed to 1.5 mm / s.
[0079] <Comparative Example 1> A photo-fabricated structure was produced in the same manner as in Example 1, except that nanoparticles were not mixed into the medium.
[0080] <Comparative Example 2> A photo-fabricated structure was produced in the same manner as in Example 2, except that nanoparticles were not mixed into the medium.
[0081] <Comparative Example 3> A photo-fabricated structure was produced in the same manner as in Example 3, except that nanoparticles were not mixed into the medium.
[0082] <Comparative Example 4> A photo-fabricated structure was produced in the same manner as in Example 5, except that nanoparticles were not mixed into the medium.
[0083] <Comparative Example 5> A photo-fabricated structure was produced in the same manner as in Example 6, except that nanoparticles were not mixed into the medium.
[0084] (Evaluation of photo-fabricated structures) For each of the stereolithographic structures of Examples 1 to 5 and Comparative Examples 1 to 5, the surface of the stereolithographic structure was observed by a scanning electron microscope (FE-SEM). (Measurement of pore area ratio) The pore area ratio of each photo-fabricated structure was calculated by the following procedure. (1) SEM photographs were taken at 5,000x magnification using a FE-SEM (JEOL, JSM-7500FA). (2) The planar area of the linear photo-fabricated structure was measured for the obtained SEM photograph. (3) Pores exposed on the surface of the photo-fabricated structure were extracted by binarization processing using Asahi Kasei Engineering Co., Ltd.'s A-Zou-kun (registered trademark), and the total planar area of each pore was calculated. (4) Using the obtained values, the pore area ratio was calculated according to the following formula (I). Pore area ratio (%) = (total pore area / area of photo-lithographic structure) × 100 (I)
[0085] Table 1 shows the evaluation results of Examples 1 to 6 and Comparative Examples 1 to 5. In the table, "no precipitation" means that the stereolithographic structure was not precipitated by laser irradiation.
[0086] [Table 1]
[0087] According to the above results, the presence of nanoparticles with high thermal conductivity in the photo-molding material allowed a photo-molded structure with a pore area ratio of 12.8% or less to be obtained. On the other hand, it was found that a conventional photo-molded structure formed from a material that does not contain nanoparticles had a high pore area ratio of 27.7% or more. That is, the photo-molded material contains nanoparticles with high thermal conductivity, so that the pore area ratio can be reduced by about 68% to about 81% compared to a conventional photo-molded structure manufactured under the same conditions except that it does not contain nanoparticles. From the above, according to the present invention, a photo-molded structure with fewer pores can be provided by containing nanoparticles. Therefore, it was found that according to the present invention, a photo-molded structure with a denser structure and excellent mechanical strength can be provided.
[0088] In addition, according to the results of Comparative Examples 4 and 5, when the laser irradiation was performed with a low laser output of 35 mW, a photo-molded structure was not formed. On the other hand, according to the results of Example 5 containing nanoparticles, the photo-molded structure was able to be precipitated even with a low laser output of 35 mW, and the obtained photo-molded structure showed a very low pore area ratio of 0.1%. This shows that the presence of nanoparticles allows the thermal energy to be suitably concentrated, so that a photo-molded structure can be suitably formed even with a low-output laser. From the above, it was found that according to the present invention, a photo-molded structure with excellent mechanical strength can be manufactured using a laser with a lower output.
[0089] In addition, even when the laser was irradiated at a high scanning speed of 1.5 mm / s, no photo-molded structure was formed. On the other hand, according to the results of Example 5, even at a scanning speed of 1.5 mm / s, a photo-molded structure having a low pore area ratio of 6.2% was obtained. This shows that the presence of nanoparticles allows the thermal energy to be suitably concentrated, so that even when the laser irradiation time at one location is short and the amount of applied light energy is small, a photo-molded structure can be suitably formed. From the above, it was found that according to the present invention, a photo-molded structure with excellent mechanical strength can be manufactured at a faster laser scanning speed.
[0090] Although the embodiments of the present invention have been described above, they are merely typical examples. Therefore, the present invention is not limited to these, and it will be easily understood by those skilled in the art that various modifications are possible without departing from the scope of the present invention.
[0091] The above-described embodiment of the present invention includes the following preferred aspects. <1> A photo-fabricated structure containing one or more metal elements as a main component, The photo-molded structure has a pore area ratio of 20% or less. <2> Pores are present on at least one of the surface and the interior of the photo-modeled structure, The area ratio of the pores in the photo-molded structure is 0.05% or more and 15% or less. <1> Photo-induced lithography structure. <3> The metal element is at least one selected from the group consisting of Fe, Co, Cu, Mn, Ni, Zn, Ti and Ba. <1> or <2> Photo-induced lithography structure. <4> The photo-fabricated structure is a composite oxide containing two or more of the metal elements, The two or more metal elements are selected from the group consisting of Fe, Co, Cu, Mn, Ni, Zn, Ti and Ba. <1> ~ <3> The photolithographic structure may be any of the following: <5> Further comprising nanoparticles having an average particle size on the order of nanometers; The thermal conductivity of the nanoparticles is 10 W / m K or more and 500 W / m K or less. <1> ~ <4> The photolithographic structure may be any of the following: <6> The content of the nanoparticles is 1.0×10 -3 Weight% or more 1.0×10 -2 % by weight or less, <5> Photo-induced lithography structure. <7> The nanoparticles are gold nanoparticles. <5> or <6> Photo-induced lithography structure. <8> Contains unsintered regions on at least one of the surface and the interior; <1> ~ <7> The photolithographic structure may be any of the following: <9> A metal material containing metal ions of one or more metal elements, nanoparticles, and a medium containing the metal material and the nanoparticles, A material for stereolithography, wherein the thermal conductivity of the nanoparticles is greater than the thermal conductivity of a main component of the medium. <10> The thermal conductivity of the nanoparticles is greater than the thermal conductivity of the medium and the metal material; <9> Material for photopolymerization. <11> The medium is a liquid, a gel or a solid. <9> or <10> Material for photopolymerization. <12> The metal element is at least one selected from the group consisting of Fe, Co, Cu, Mn, Ni, Zn, Ti and Ba. <9> ~ <11> Any of the above materials for stereolithography. <13> The nanoparticles contain at least one metal element among the metal elements contained in the metal material. <9> ~ <12> Any of the above materials for stereolithography. <14> The content of the nanoparticles in the medium is 7.0×10 -6 Volume percent or more 7.0×10 -4 % by volume or less, <9> ~ <13> Any of the above materials for stereolithography. <15> The metallic material is excited with a specific wavelength. <9> ~ <14> 13. The optical shaping material according to claim 12, <16> In the optical absorption spectrum of the medium, the absorption intensity of the optical absorption originating from the nanoparticles is 3.0% or less of the peak intensity of the optical absorption spectrum of the medium. <9> ~ <15> Any of the above materials for stereolithography. <17> Further comprising a plate-shaped substrate, The medium is disposed on the substrate; The thermal conductivity of the substrate is less than the thermal conductivity of the nanoparticles. <9> ~ <16> Any of the above materials for stereolithography. <18> <9> ~ <17> A photo-molded structure manufactured from any one of the above-mentioned materials for photo-molding. <19> The method includes a step of irradiating a laser beam onto a material for optical shaping, the optical shaping material comprises a metal material containing metal ions of one or more metal elements, nanoparticles, and a medium containing the metal material and the nanoparticles; A method for manufacturing a photo-fabricated structure, wherein the thermal conductivity of the nanoparticles is greater than the thermal conductivity of a main component of the medium. <20> The method includes a step of irradiating a laser beam onto a material for optical shaping, The optical shaping material comprises a medium containing a metal material containing metal ions of one or more metal elements and nanoparticles; The thermal conductivity of the nanoparticles is greater than the thermal conductivity of the medium and the metal material; <19> A method for manufacturing a photo-fabricated structure. <21> The output of the laser light is 20 mW or more and 50 mW or less. <19> or <20> A method for manufacturing a photo-fabricated structure. [Explanation of symbols]
[0092] 10: Base material for stereolithography 11: Medium 12: Nanoparticles 15: Base material 20:Stereolithography structure 21: Poa 25: Unsintered area
Claims
1. A photo-fabricated structure containing one or more metal elements as a main component, The photo-fabricated structure has a pore area ratio of 20% or less.
2. Pores are present on at least one of the surface and the interior of the photo-modeled structure, The photo-molded structure according to claim 1 , wherein the area ratio of the pores in the photo-molded structure is 0.05% or more and 15% or less.
3. 2. The photo-fabricated structure according to claim 1, wherein the metal element is at least one selected from the group consisting of Fe, Co, Cu, Mn, Ni, Zn, Ti, and Ba.
4. The photo-fabricated structure is a composite oxide containing two or more of the metal elements, The photo-fabricated structure according to claim 1 , wherein the two or more metal elements are selected from the group consisting of Fe, Co, Cu, Mn, Ni, Zn, Ti and Ba.
5. Further comprising nanoparticles having an average particle size on the order of nanometers; The photo-fabricated structure according to claim 1 , wherein the thermal conductivity of the nanoparticles is 10 W / m·K or more and 500 W / m·K or less.
6. The content of the nanoparticles is 5.0×10 -5 Volume percent or more 5.0 x 10 -4 6. The photo-molded structure according to claim 5, wherein the content of the polymer in the polymer layer is 10% by volume or less.
7. The photo-fabricated structure according to claim 5 , wherein the nanoparticles are gold nanoparticles.
8. The photo-fabricated structure according to claim 1 , comprising an unsintered region on at least one of a surface and an interior.
9. A metal material containing metal ions of one or more metal elements, nanoparticles, and a medium containing the metal material and the nanoparticles, A material for stereolithography, wherein the thermal conductivity of the nanoparticles is greater than the thermal conductivity of a main component of the medium.
10. The stereolithography material according to claim 9 , wherein the thermal conductivity of the nanoparticles is greater than the thermal conductivity of the medium and the metal material.
11. The stereolithography material according to claim 9 , wherein the medium is a liquid, a gel, or a solid.
12. 10. The optical shaping material according to claim 9, wherein the metal element is at least one selected from the group consisting of Fe, Co, Cu, Mn, Ni, Zn, Ti, and Ba.
13. The optical shaping material according to claim 9 , wherein the nanoparticles contain at least one type of metal element among the metal elements contained in the metal material.
14. The content of the nanoparticles in the medium is 7.0×10 -6 Volume percent or more 7.0 x 10 -4 10. The optical shaping material according to claim 9, wherein the content of the ionic liquid is 10% by volume or less.
15. The stereolithography material according to claim 9 , wherein the metallic material is excited with a specific wavelength.
16. 10. The optical shaping material according to claim 9, wherein in the optical absorption spectrum of the medium, an absorption intensity of the optical absorption originating from the nanoparticles is 3.0% or less of a peak intensity of the optical absorption spectrum of the medium.
17. Further comprising a plate-shaped substrate, The medium is disposed on the substrate; The stereolithography material according to claim 9 , wherein the thermal conductivity of the base material is lower than the thermal conductivity of the nanoparticles.
18. A photo-molded structure manufactured from the photo-molding material according to any one of claims 9 to 17.
19. The method includes a step of irradiating a laser beam onto a material for optical shaping, the optical shaping material comprises a metal material containing metal ions of one or more metal elements, nanoparticles, and a medium containing the metal material and the nanoparticles; A method for manufacturing a photo-fabricated structure, wherein the thermal conductivity of the nanoparticles is greater than the thermal conductivity of a main component of the medium.
20. The method for manufacturing a photo-printed structure according to claim 19 , wherein the thermal conductivity of the nanoparticles is greater than the thermal conductivity of the medium and the metal material.
21. The method for producing a photo-molded structure according to claim 19, wherein the output of the laser light is 20 mW or more and 50 mW or less.
Citation Information
Patent Citations
Thin film forming method with laser beam
JP2002069665A